Xenopus oocytes as a heterologous expression system for analysis of tight junction proteins. Issue 4 (15th January 2019) - Vitzthum, Constanze; Stein, Laura; Brunner, Nora; Knittel, Ria; Fallier‐Becker, Petra; Amasheh, Salah
ABSTRACT: Claudins (cldns) represent the largest family of transmembrane tight junction (TJ) proteins, determining organ‐specific epithelial barrier properties. Because methods for the analysis of multiple cldn interaction are limited, we have established the heterologous Xenopus laevis oocyte expression system for TJ protein assembly and interaction analysis. Oocytes were injected with cRNA encoding human cldn‐1, ‐2, or ‐3 or with a combination of these and were incubated in pairs for interaction analysis. Immunoblotting and immunohistochemistry were performed, and membrane contact areas were analyzed morphometrically and by freeze fracture electron microscopy. Cldns were specifically detected in membranes of expressing oocytes, and coincubation of oocytes resulted in adhesive contact areas that increased with incubation time. Adjacent membrane areas revealed specific cldn signals, including "kissing‐point"–like structures representing homophilic trans ‐interactions of cldns. Contact areas of oocytes expressing a combination markedly exceeded those expressing single cldns, indicating effects on adhesion. Ultra‐structural analysis revealed a self‐assembly of TJ strands and a cldn‐specific strand morphology.—Vitzthum, C., Stein, L., Brunner, N., Knittel, R., Fallier‐Becker, P., Amasheh, S. Xenopus oocytes as a heterologous expression system for analysis of tight junction proteins. FASEB J. 33, 5312–5319 (2019). www.fasebj.org